Rcihard N. Haass, Foreign Policy Begins at Home: The Case for Putting America’s House in Order - Ms. Farzana Siddique (CISS Insight Journal, 2014)
Richard N. Haass, the author of the book Foreign Policy Begins at Home: The Case for Putting America's House in Order is the president of Council on Foreign Relations, a position he has held for over twelve years. Council on Foreign Relations is a well-known independent think tank working in the areas of foreign policy and international relations. Dr. Haass is the author of twelve books on foreign policy and has also written a book on management. Beside his work in Council on Foreign Relations Dr. Haass has worked in various capacities for almost equal number of years in the US administration. In the Bush Administration he was Director of Policy Planning and Advisor to the Secretary of State, Collin Powell.This book is divided into three parts. The first part of the book titled ‘The Return of history,’ has been written in the perspective of hope for world peace and global stability generated by the end of the Cold War. It discusses major features of international political order after the Cold War with focus on post 9/11 era. The author points out that despite assertions by some authors on the uni-polarity of the world in the absence of challenges posed to US security by the then USSR, it is not a uni-polar world. In Dr. Haass’ opinion the dominant feature of the first half of 21st century will be non-polarity though the USA will retain its primacy in the world affairs. He is critical of American war on Iraq which in his opinion has weakened American position in the world. Though the author is supportive of war in Afghanistan after 9/11 terming it a war of necessity, but he is critical of the manner in which it was handled by the policy makers. The author opines that America is presently facing a number of internal problems and advises its policy makers to focus on internal issues rather than expanding its foreign policy agenda.